Development of Cardboard Puppet Teaching Media on General Attack Materials March 1, 1949 at SMA Negeri 1 Bukateja Purbalingga - Haifani, Ayun; Utomo, Cahyo Budi; Sodiq, Ibnu (Universitas Negeri Semarang, 2020)
This research is the development of wayang into creative learning media. The goal is to reduce the problems covering the main learning conditions of history in SMA N 1 Bukateja. The use of Media with puppet cartons is expected to make the students more interested, and the main can help the students to understand the history material. This research is a type of research and development (research and development) with experimental design. The subjects in the study were students in class XI IPS SMA Negeri 1 Bukateja. Collecting data from this research is using field analysis (field research), observation, and interviews. The development of products as a medium of teaching cartoon puppets has been through the validation process twice before being applied in the learning process. Validation done by media and material experts with the eligibility level is well-used without revision. The research shows that the development of carton media on the material of the general attack on March 1, 1949, proved effective and feasible to be applied in learning history. The results showed that the experimental class had an average score of 88, better than the control class, which only got a score of 77. In conclusion, this media is a creative and new medium in education that utilizes puppets. In addition, this media indirectly introduces Indonesia's indigenous culture to today's young generation.